1998
DOI: 10.1093/carcin/19.7.1247
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-related increase of O6-methylguanine-DNA methyltransferase expression in human lung carcinomas

Abstract: Eighty-three non-small cell lung carcinomas (NSCLC) of previously untreated patients were analysed for expression of O 6 -methylguanine-DNA methyltransferase (MGMT) by means of immunohistochemistry. Expression of MGMT was detected in 62 of 83 tumours (75%). There was a significant difference in MGMT staining between smokers and non-smokers (P ⍧ 0.001). Tumours of smokers expressed more frequently MGMT than tumours of nonsmokers. There was a trend of MGMT expression to be higher in tumours of patients smoking >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
5

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 23 publications
5
24
5
Order By: Relevance
“…Several studies have demonstrated that the inactivation of a repair gene by promoter hypermethylation resulted in the impaired expression of MGMT protein [2,9,14,18,22]. The loss of protein was uniform in lymphoma, but tumors of the colon, lung, and brain showed cellular heterogeneity or stronger expression than adjacent normal tissues [14,23,27,36,41,49]. According to Kokkinakis et al [23], MGMT protein was absent in the hyperplastic and normal components of pancreatic tissues, but invariably present in dysplastic foci and especially strong in the invasive component of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the inactivation of a repair gene by promoter hypermethylation resulted in the impaired expression of MGMT protein [2,9,14,18,22]. The loss of protein was uniform in lymphoma, but tumors of the colon, lung, and brain showed cellular heterogeneity or stronger expression than adjacent normal tissues [14,23,27,36,41,49]. According to Kokkinakis et al [23], MGMT protein was absent in the hyperplastic and normal components of pancreatic tissues, but invariably present in dysplastic foci and especially strong in the invasive component of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 However, MGMT inactivation may be an early event in tumorigenesis conferring an increased susceptibility to nitrosamines and other alkylating agents. 15 It was previously demonstrated that cytosine methylation enhances guanine alkylation by a variety of bulky carcinogens (benzo(a)pyrene diol epoxide, AFB 1 8,9-epoxide, benzo(g)chrysene diol epoxide and N-acetoxy-2-acetylaminofluorene).…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis, several resistance proteins and additional resistancerelated factors were changed in resistant NSCLC in comparison to sensitive carcinomas. The reason for this concomitant expression of different factors may be the result of inducing a cascade of resistance-related gene products that can be triggered by environmental factors such as smoking (Volm et al, 1991Mattern et al, 1998). Another possible explanation is that lung cancer is mostly detected at a relatively late stage.…”
Section: Discussionmentioning
confidence: 99%